‘Ilm al-Tafsir and critical discourse analysis: a methodological comparison - Munif Zarirruddin Fikri Nordin, (Penerbit UKM, 2015)
The methodology of ‘Ilm al-Tafsir and the methodology of Critical Discourse Analysis (CDA) highlight the similarities and differences in leveraging the text as research data beyond the level of the text’s structure. Questions on similarities and differences between methodologies are addressed in the present study. This study, therefore, compares the similarities and the differences between the methodology of ‘Ilm al-Tafsir and the methodology of CDA. Based on the comparison, the present study also constructs a religious discourse analysis model. The selected methodology of ‘Ilm al-Tafsir is al-Sabuniy’s in Safwat al-Tafasir (1979), while the chosen methodology of CDA is Fairclough’s 3D (1992; 1995). The universal principle of discourse and the linguistic goals in the philosophy of language is applied in the analysis. Similarities and differences were identified in the production, meaning and interpretation. The findings strongly suggest that the two methodologies have circumstances which lead to the use of language, the production of language, the features of texts, the nature of meaning and the means of interpretation. One of the main focuses of the comparison is on the differences that constitute barriers to the adoption of CDA for religious discourse analysis, specifically the critical approach towards the sickle and the fixed elements. The obstacles to this alternative are presented in order to prove that there is a linguistic approach that is capable of linking language with social elements. The findings thus have implications for the relatively new methodology of religious discourse in linguistic studies.